Isolation of caffeine from the seeds of Leucaena leucocephala (Lam.) De Wit. (Family Leguminosae) - Evangelista, Liza F.
Caffeine may be isolated from roasted ipil-ipil seeds (Leuucaena leucocephala (Lam.) De Wit) by refluxing with alcohol for 6 hours.